Some Evidence on the Importance of Sticky Prices - Bils, Mark; Klenow, Peter J. (Journal of Political Economy, 2004)
We examine the frequency of price changes for 350 categories of goods and services covering about 70 percent of consumer spending, on the basis of unpublished data from the Bureau of Labor Statistics for 1995–97. In comparison with previous studies, we find much more frequent price changes, with half of prices lasting less than 4.3 months. Even excluding temporary price cuts (sales), we find that half of prices last 5.5 months or less. We also find that the frequency of price changes differs dramatically across goods. Compared to the predictions of popular sticky‐price models, actual inflation rates are far more volatile and transient for sticky‐price goods.